Switchable diurnal radiative cooling by doped VO2 - Minkyung Kim; Dasol Lee; Younghwan Yang; Junsuk Rho (Opto-Electronic Advances, 2021)
This paper presents design and simulation of a switchable radiative cooler that exploits phase transition in vanadium dioxide to turn on and off in response to temperature. The cooler consists of an emitter and a solar reflector separated by a spacer. The emitter and the reflector play a role of emitting energy in mid-infrared and blocking incoming solar energy in ultraviolet to near-infrared regime, respectively. Because of the phase transition of doped vanadium dioxide at room temperature, the emitter radiates its thermal energy only when the temperature is above the phase transition temperature. The feasibility of cooling is simulated using real outdoor conditions. We confirme that the switchable cooler can keep a desired temperature, despite change in environmental conditions.